Optimalisasi Penggunaan Masker pada Penerapan Pembelajaran Hibrid di Sekolah Luar Biasa - Prima Daniyati Kusuma (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Covid-19 cases in children are a matter of concern. Children are one of the most vulnerable groups to be infected with Covid-19. Children with special needs with comorbidities, have a higher risk when they are exposed to Covid-19. The high mortality rate of Covid-19 in children in Indonesia can be caused because the child has a history of comorbidities and then contracted Covid-19. In addition, services for handling pediatric patients in a number of health facilities are still not optimal. A number of schools in various regions in Indonesia have started to organize limited face-to-face learning, namely using hybrid learning methods. Responding to this, the school must prepare and ensure the creation of a safe learning environment for children when they have to come to school, one way is by using masks properly and correctly. This community service activity was carried out at the SLB N Pembina Yogyakarta. The service method uses lecture, discussion and demonstration methods. The results achieved are the implementation of health counseling activities, the manufacture of pocket book media, and an increase in students' knowledge about how to use masks properly and correctly.